Microbial Composition and Co-occurrence Patterns in the Gut Microbial Community of Normal and Obese Mice in Response to Astaxanthin - Gao, Yuan; Liu, Fang; Li, Robert W.; Li, Chunjun; Xue, Changhu; Tang, Qingjuan (Frontiers in Microbiology, 2021)
The changes and interaction of gut microbiota, which responses to dietary supplements, play critical roles on improving human health. The modulating effect of astaxanthin on gut microbiota has been reported. However, little is known about the co-occurrence patterns among microbial taxa in response to astaxanthin. In this study, the gut microbial composition, co-occurrence patterns and microbial correlations with physiological parameters in astaxanthin-fed normal and obese mice were studied. Astaxanthin altered the microbial composition and co-occurrence patterns in normal and obese mice. Furthermore, astaxanthin gave more profound impacts on microbiota in obesity, when compared with normal mice. In group A (normal or obese mice supplemented with astaxanthin), the abundance of Acinetobacter was decreased and the Alistipes was increased by astaxanthin, which were also occurred in MA group (obese mice supplemented with astaxanthin). An OTU (GreenGeneID# 4029632) assigned to the genus Bacteroides acted as a connector in the global network of A and MA groups. It may play critical roles in bridging intimate interactions between the host and other bacteria intervened by astaxanthin. Several modules correlated with physiological parameters were detected. For example, Modules A12 and MA10 were significantly and negatively correlated with lipopolysaccharide (LPS) and fasting blood glucose (FBG) levels, respectively. A positive correlation was found between node connectivity of the OTUs belonging to Clostridiaceae with LPS in obese mice, which indicated the role of Clostridiales as a potential pathological marker. Our findings provided a new interpretation of the role of astaxanthin in health, and may contribute to further researches on microbial community engineering.